Clinical experience and complications with limited pleural dissection combined with a novel, simplified technique for thoracic Redon-like drain in vertebral body tethering - Courvoisier, Aurélien; Maximin, Marie-Christine; Daniel, Olivier; Gouron, Richard; Evain, Jean-Noël; Baroncini, Alice (Spine deformity, 2024)
Purpose To report on our experience with a simplified, suction-bottle-drain technique of thoracic drain (Redon-like) combined with fully thoracoscopic vertebral body tethering (VBT) and a limited pleural approach, with particular focus on the rate of pulmonary complications. Methods A retrospective study was performed on all consecutive patients who underwent VBT for adolescent idiopathic scoliosis. For all subjects, a 10G Redon drain, an active drain system consisting of a perforated tube and a suction bottle, was placed intrathoracically and tunneled under the skin. All drains were removed on the first postoperative day. Perioperative and postoperative data such as type of access, length of surgery, amount of fluid collection in the drain, and length of hospital stay were collected. The type and number of pulmonary complications occurring in the first 3 months after surgery, along with their symptoms and management, were recorded. Results One Hundred eighty-two patients were included in the analysis. The mean length of surgery was 97 min (75–120). The average fluid collection in the drain was 30 ml (5–50), the mean length of hospital stay was 3 days (2–4). During the observation period, pulmonary complications occurred in five patients (2%). Two patients presented an aseptic right pleural effusion; for two patients, a residual pneumothorax was diagnosed on the X-rays in the recovery room and one patient developed a chylothorax. All patients recovered without sequelae. Conclusion The simplified, Redon-like drain combined with a fully thoracoscopic VBT and limited pleural approach seems a safe and effective alternative to the chest drain. This technique allows to remove the drain on the first postoperative day, thus simplifying the management of the patients and improving their comfort.